Die verhale van kinders wat seksuele misbruik oorleef het: "n Pastoraal-narratiewe ondersoek - Malan, C. N. (HTS teologiese studies, 2006)
The stories of children who survived sexual abuse: A pastoral-narrative inquiryThis article presents the stories of two survivors. These stories show how the survivors were invited to capture “sparkling events” and developed them into preferred stories, and how by living in these stories, they could experience themselves in preferred and satisfactory ways. This article introduces various ways by which the news of empowerment and transformation can be circulated. The stories of these survivors were re-written and transformed by a community of shared experience, and it was through this experience that they could start dreaming about the transformation of their communities realizing how their stories and their journey had the ability to touch and transform the lives of numerous other survivors.